2021
DOI: 10.1021/jacs.1c04426
|View full text |Cite
|
Sign up to set email alerts
|

Identifying G-Quadruplex-DNA-Disrupting Small Molecules

Abstract: The quest for small molecules that strongly bind to Gquadruplex-DNA (G4), so-called G4 ligands, has invigorated the G4 research field from its very inception. Massive efforts have been invested to discover or rationally design G4 ligands, evaluate their G4interacting properties in vitro through a series of now widely accepted and routinely implemented assays, and use them as innovative chemical biology tools to interrogate cellular networks that might involve G4s. In sharp contrast, only uncoordinated efforts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 100 publications
8
67
0
Order By: Relevance
“…G4Qs have therefore received considerable attention over the last twenty years due to their involvement in the regulation of cellular processes including replication, transcription and translation. [ 10 , 11 , 12 , 13 , 14 , 15 ] Dysregulation of G4Q formation and their binding proteins, which assist them in regulating the equilibrium between their structured and unstructured/unfolded forms, due to mutations or through the alteration of their stability by environmental factors (for example, by changes in intracellular solution conditions or by G4Q‐stabilization induced by a ligand), have been found to contribute to many human pathologies, including neurodegenerative diseases, cancer, and microbial infections. [ 4 , 5 , 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…G4Qs have therefore received considerable attention over the last twenty years due to their involvement in the regulation of cellular processes including replication, transcription and translation. [ 10 , 11 , 12 , 13 , 14 , 15 ] Dysregulation of G4Q formation and their binding proteins, which assist them in regulating the equilibrium between their structured and unstructured/unfolded forms, due to mutations or through the alteration of their stability by environmental factors (for example, by changes in intracellular solution conditions or by G4Q‐stabilization induced by a ligand), have been found to contribute to many human pathologies, including neurodegenerative diseases, cancer, and microbial infections. [ 4 , 5 , 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…32 It is only recently (while this manuscript was under review) that Monchaud and co-workers have published a G4-helicase based destabilization assay. 44 Nevertheless, there are small molecules that have been reported to destabilize G4s. For example, TMPyP4 disrupted the G4 structure in the Fragile X FMR1 gene, 42 and in the MT3 endopeptidase mRNA sequence; 45 a triarylpyridine derivative disrupted G4 in the cKit-1 and 2 sequences; 46 an anthrathiophenedione, 47 and a stiffstilbene derivative was shown to unfold a sodium form of telomeric G4.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, molecular dynamics and NMR studies suggested that STI binds to G4 grooves and intercalates between G-quartets, which may lead to disruption of the G-quartets H-bond network [327]. Very recently, the ability of a set of chemically diverse G4 ligands to disrupt G4 structures was investigated using several biophysical and biochemical methods [329]. The authors concluded that the effect of G4 ligands on the G4 structure is strongly dependent on the technique and concentration of the ligand, in agreement with a previous study [330].…”
Section: Ligand-induced Quadruplex Stabilization or Destabilizationmentioning
confidence: 99%
“…Very recently, the ability of a set of chemically diverse G4 ligands to disrupt G4 structures was investigated using several biophysical and biochemical methods [ 329 ]. The authors concluded that the effect of G4 ligands on the G4 structure is strongly dependent on the technique and concentration of the ligand, in agreement with a previous study [ 330 ].…”
Section: Ligand-induced Effectsmentioning
confidence: 99%
See 1 more Smart Citation